Slavery in Islam: An Islamic Sufi Approach - Bidabad, Bijan; Tabatabaei, Mehdi (International Journal of Shari’ah and Corporate Governance Research, 2019)
In this paper, the history of slavery in the pre-Islamic era is considered first, and then the definitions used in that period are compared with the Islamic definition of slavery. Generally, in concept and reality, the definition of slavery from the Islamic viewpoint has essential differences with slavery in the ancient world, and the treatment with slaves was also totally different. Unlike the abolition of slavery in most countries which accompanied with war, roughness and social damages, the decided policies of Islam were based on the gradual deletion of slavery from the society to achieve the least social turbulence. Actually, because the input to the slavery system in Islam was narrow, and the output of the slavery system was wide; the phenomenon of slavery was gradually deleted in Islamic nations.